Obesity-Related Chronic Kidney Disease: From Diagnosis to Treatment - Elena Avgoustou; Ilektra Tzivaki; Garyfalia Diamantopoulou; Tatiana Zachariadou; Despoina Avramidou; Vasileios Dalopoulos; Alexandros Skourtis (Diagnostics)
Obesity has emerged as a global epidemic with far-reaching health complications, including its role as an independent risk factor for chronic kidney disease (CKD). Increasing evidence suggests that obesity contributes to CKD through multiple mechanisms, including chronic inflammation, hemodynamic alterations, insulin resistance, and lipid accumulation. These processes can culminate in histopathological changes collectively referred to as obesity-related glomerulopathy (ORG). This review aims to provide a comprehensive overview of the current knowledge regarding the prevalence, clinical manifestations, and pathophysiology of ORG. Furthermore, we emphasize the importance of identifying key biomarkers that facilitate the early detection of ORG. Finally, we explore emerging therapeutic strategies that offer promise in mitigating this growing global health crisis.